KECERDASAN EMOSIONAL MAHASISWA ANGGOTA ORGANISASI TINGKAT FAKULTAS PROGRAM STUDI BIMBINGAN KONSELING - Deliati Deliati; Elfrianto Elfrianto; Halimah Tussa’diah (Universitas Negeri Medan, 2022)
Emotional Intelligence of Student Organizational Members at the Faculty of Counseling Guidance Study Program. Throughout The Span Of Life Lived, From Birth To Death, Humans Need Other People. Various Kinds Of Ways In The Process Of Interaction Will Be Found Throughout Human Life. One Individual To Another, One Environment To Another Will Have A Different Way Of Interacting. Students' Social Skills Tend To Decrease Because They Only Communicate With A Few Friends. Some Students Feel Bored, Tired, Stressed, Scared And Relaxed Which Causes Them To Experience Difficulties In Completing Coursework, Difficulty Focusing When Paying Attention To Lecturers Teaching, Decreased Motivation In Doing Coursework. Universities Have An Academic Responsibility To Prepare Students To Face The Realities Of A Productive And Valuable Life. The Learning Process In Tertiary Institutions Is An Important Journey That Students Need To Go Through. The Research Design Used In This Research Is Qualitative Research. The Qualitative Research Design Was Chosen Because It Is Natural And Presented As It Is Without Elements Of Manipulation Or Special Treatment Of The Research Object. Emotional Intelligence Is A Strong Impulse That Directs Humans To Do Something. Each Emotion Can Direct A Different Action. Humans Have Two Sources Of Thinking, Namely Emotion And Reason. Emotions Take Action On Impulses Before Reason Has A Chance To Take Control Of The Situation.